Research and Development of New Vibration and Noise Reduction Methods and their Manufacturing Technology - Gavasheli, Levan; Gavasheli, Anri (Annals of Mathematics and Physics, 2026)
Based on the theoretical research conducted in our laboratory, a technology for producing new flexible-damping materials has been developed. These flexible-damping elements are characterized by an increased ability to absorb harmful energies and high resistance to cyclic loads, while under static and dynamic loads, their 'stress-displacement' behavior exhibits a hysteresis characteristic in a hyperbolic form. These advantages of flexible-damping elements allow them to be effectively used in the production of vibration- damping devices for heavy machinery, where vibration levels often exceed permissible limits, especially when operating in harsh environmental conditions.